QUALITY OF WORK LIFE WITH REFFRENCE TO LIFE INSURANCE CORPORATION OF INDIA, HYDERABAD - S. Sirisha, B. Malleswari, Dr.Sk.Shamshad Ahamed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Any organization's ability to draw in, hire, inspire, and keep its employees is crucial to its success. Organizations nowadays must be more adaptable if they want to be able to grow their workforce and value employee dedication. LIC is a public sector Corporation its HR policies are well framed but due to the entrance of Multi-national As insurance companies it is facing a lot of competition. So, there are challenges to maintain their leadership in life insurance sector. 96% of the respondents have stated that their present compensation is adequate. The management may decide the compensation through agreements with the employees union as a result salaries are fixed for all cadres of employees